Effect of Yogic management on Gastroesophageal Reflux DiseaseGERD - Malik, Saloni; Kumar Sharma, Rahul; Kumar, Rupesh; Kumar Agrawal, Manan; Indumati, T. (International Journal of Psychosocial Rehabilitation, 2024)
Yoga is an ancient Indian Science of living which was developed by the sages to helpmanifest humanpotential to its maximum. It gives a complete holistic physical, mental,emotional, social andspiritual development to an individual. Thus, it can be practised by allirrespective of thelevel they are in. Yoga can help create a healthy mind bodyconnection,improving their co-ordination, behaviour, moods, physical activity and socialabilities.1Yoga methods including Pranayama are the best ways to prevent many diseases and theirprogression.There are many methods including pranayama which show effects on many chronicdiseases where gastroesophageal reflux disease is one of them.2This is most effective on psychosomatic aliments. It cannot only prevent and cure diseasesbut also promotes positive health.